Systematics of Civil Law In Indonesia and The Netherlands - Abdul Hakim; Indri Arsalnah (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
This study examines the systematics of civil law in Indonesia and the Netherlands through a normative legal research approach. Civil law serves as the basic framework that regulates relationships between individuals in society. The Indonesian civil law system is historically rooted in Dutch law, specifically the Burgerlijk Wetboek (BW), which was introduced during the colonial period. However, over time, Indonesian civil law has evolved to accommodate elements of customary law and Islamic law, resulting in a legal system that is pluralistic and unique. This study uses a statutory approach, a comparative approach, and a conceptual approach, relying on primary, secondary, and tertiary legal materials collected through library research. The analysis is conducted qualitatively through legal interpretation and comparative methods to identify similarities and differences in the legal systems of the two countries. The results show that Indonesia still largely refers to the classical structure of civil law consisting of four books: on persons, objects, obligations, and evidence, which originated from the old Dutch BW. In contrast, the Netherlands has made significant reforms to its civil law system through the Nieuw Burgerlijk Wetboek, which adopts a more modern, flexible, and systematic approach. This study concludes that although both legal systems share a common historical basis, there are significant differences in terms of development and modernization. The Indonesian civil law system is still in a transitional stage, necessitating comprehensive legal reform to create a more adaptive, integrated, and responsive legal system to the needs of modern society.